2012
DOI: 10.3389/fimmu.2012.00127
|View full text |Cite
|
Sign up to set email alerts
|

Chemokines and the Signaling Modules Regulating Integrin Affinity

Abstract: Integrin-mediated adhesion is a general concept referring to a series of adhesive phenomena including tethering-rolling, affinity, valency, and binding stabilization altogether controlling cell avidity (adhesiveness) for the substrate. Arrest chemokines modulate each aspect of integrin activation, although integrin affinity regulation has been recognized as the prominent event in rapid leukocyte arrest induced by chemokines. A variety of inside-out and outside-in signaling mechanisms have been related to the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
60
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(60 citation statements)
references
References 83 publications
0
60
0
Order By: Relevance
“…Notably, most of the studies describe proadhesive signaling events, even when antiadhesive signals likely have an equally relevant role in leukocyte recruitment, for example, during the on-off turnover of integrin activation necessary for cell motility and transmigration. To date, few signaling molecules have been shown to negatively regulate leukocyte integrin activation; these include PKA (34), RHOH (35), CDC42 (10,36), SRC (37-39), H-RAS (40), ILK (41), FAM65B (42), and CAPN2 (43), with only CDC42 investigated according to the previously formalized four criteria (2). In the present study, fully compliant with these criteria, we show that PTPRG is a novel negative regulator of LFA-1 high-affinity-state triggering and mediated arrest by chemoattractants in human primary monocytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, most of the studies describe proadhesive signaling events, even when antiadhesive signals likely have an equally relevant role in leukocyte recruitment, for example, during the on-off turnover of integrin activation necessary for cell motility and transmigration. To date, few signaling molecules have been shown to negatively regulate leukocyte integrin activation; these include PKA (34), RHOH (35), CDC42 (10,36), SRC (37-39), H-RAS (40), ILK (41), FAM65B (42), and CAPN2 (43), with only CDC42 investigated according to the previously formalized four criteria (2). In the present study, fully compliant with these criteria, we show that PTPRG is a novel negative regulator of LFA-1 high-affinity-state triggering and mediated arrest by chemoattractants in human primary monocytes.…”
Section: Discussionmentioning
confidence: 99%
“…A number of protein and lipid kinases have been shown to regulate the proadhesive signaling network triggered by chemoattractants (2). In this context, we have recently shown that protein tyrosine kinases (PTKs) of the JAK family are upstream transducers linking the chemokine receptor CXCR4 to the hierarchical activation of Rho and Rap small GTPases, thus controlling integrin affinity upregulation and homing to secondary lymphoid organs of T lymphocytes (3).…”
mentioning
confidence: 99%
“…The affinity of integrins, such as CR3, to their ligands is controlled by G-protein-coupled receptor-initiated inside-out signaling in leukocytes (45). Hence, one may hypothesize that enhanced CR3 activation triggered by C5a may result from the G-protein-coupled receptor C5aR-mediated inside-out signaling in PMN.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with these functional observations, the expression of the macrophage scavenger receptor CD36 and the major lipid droplet protein ADRP was not modified by Arhgef1 deletion (Supplemental Figure 5) Figure 2B). β 2 Integrin activation results in a conformational change that depends on both RhoA-and Rap-dependent signaling (18)(19)(20). This conversion to a high-affinity open conformation leads to the formation of the epitope for the 24 antibody (mAb 24).…”
Section: Arhgef1mentioning
confidence: 99%